The importance of nominating the beneficiaries in life insurance policy / Noor Fariza Baharin - Baharin, Noor Fariza (Faculty of Business and Management, 2010)
This thesis is study about the importance of nominating the beneficiaries in life insurance policy. It will briefly explain the information regarding on the background of the company which is MCIS ZURICH Insurance Berhad, vision and mission, the business portfolio, customer based, the products of the company, the organization’s financial statement and profits and the issue related on nomination. The researcher enclosed about the objective of the study. The researcher also explains what is the problem that exist in life insurance industry especially when the policyholder makes a death claim if there is no beneficiaries or nominee registered for life insurance policy. For the second chapter, the researcher will explain about the facts of all the procedures and the information about the nomination. The main purpose of this case study is for study the importance of nominating nominee and the effect if the policyholders not register the nominee. In this chapter, the researcher enclosed details about the importance of register nominee or beneficiaries, to differentiate if the policyholder nominating nominee with not nominating the nominee, the types of nomination, what is better between both types, and to investigate the process or procedures for death claim if have and not have nominating in life insurance. For next chapter, the researcher gets all the information by doing an interview with experience staff of the company, through observation of pending claim settlement case of the company and by using secondary data such as from the company annual report and internet. For finding the researcher compare the fact with the company practising related on the issue that have been discuss. Gap identification between the facts and what the company had done for the first process when the policyholders buy the life insurance policy about the awareness of nomination. At last of the thesis, can see either what the researcher purpose can be achieve or not.